Developing Contextual Learning Videos on Course of Administration Education Research Methodology - Muhyadi, Muhyadi; Sutirman, Sutirman; Kistiananingsih, Isti (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aimed to produce and determine the feasibility of contextual learning video on course of Administration Education Research Methodology. The research method was research and development of ADDIE model. The stages of this research and development consisted of Analysis, Design, and Development. The data collection techniques in analysis stage were interview and observation, while questionnaire was used in development stage. Data collection instruments were inventory questionnaires with rating scales. Data analysis technique was descriptive analysis with quantitative and descriptive approaches. Descriptive techniques were used to analyze the results of problems and learning components of Office Administration Education Research Methodology. Quantitative techniques were used to analyze data from experts. Validation of developed contextual learning media involved media expert and material expert. The conclusions of the particular study are: 1) this study has produced a contextual learning video on course of Administration Education Research Methodology with material of research proposal in topic of Introduction; 2) according to the assessment of media experts and material experts, the developed learning video has a criteria of very feasible.